Characterisation of Cassava Peel-Derived Silica at Different Combustion Temperatures - Mohamad Firdaus Dzilikhram Mohamad Fatahiyudin,; Kamarul Azhar Kamarudin,; Mohamed Nasrul Mohamed Hatta,; Muhammad Zaid Ahmad Sapian,; Ahmad Sufian Abdullah,; Mohd Syazwan Solah, (International Journal of Integrated Engineering, 2025)
The growing need for sustainable materials and the environmental burden of agro industrial waste highlight the urgency of transforming biomass into high value resources. Cassava peel, typically discarded as waste, contains silica a valuable mineral composed of silicon and oxygen. This study looks at the possibility of using cassava peel, which is a common waste product from agriculture and industry, as a long-term source of high-purity silica by controlled burning (400–800 °C). Acid leaching and drying process. FTIR, SEM, and TGA were used to look at the structural and thermal properties of the silica. The results showed that silica produced at 600–700°C had the best properties, with the 700°C sample achieving the highest silica yield of 54.3%, silicon content of 41.45wt%, and demonstrating sharp FTIR peaks at 1021cm?¹ and 898cm?¹ indicating a well-formed amorphous structure. It also exhibited the lowest total weight loss in TGA analysis and a moderate residue of 14.07%, confirming superior thermal stability and high purity. These properties are comparable to those of commercial silica, suggesting its potential as a cost-effective and environmentally friendly filler for polymers. This also shows how useful agricultural waste can be in developing sustainable materials engineering.